Role of MicroRNA in the Diagnosis and Management of Hepatocellular Carcinoma - Ziogas, Ioannis A.; Sioutas, Georgios; Mylonas, Konstantinos S.; Tsoulfas, Georgios (MicroRNA, 2020)
Introduction: Hepatocellular Carcinoma (HCC) is one of the most common malignant tumors in the world and comes third in cancer-induced mortality. The need for improved and more specific diagnostic methods that can detect early-stage disease is immense, as it is amenable to curative modalities, while advanced HCC is associated with low survival rates. microRNA (miRNA) expression is deregulated in HCC and this can be implemented both diagnostically and therapeutically. Objective: To provide a concise review on the role of miRNA in diagnosis, prognosis, and treatment of HCC. Methods: We conducted a comprehensive review of the PubMed bibliographic database. Results: Multiple miRNAs are involved in the pathogenesis of HCC. Measurement of the levels of these miRNAs either in tumor tissue or in the blood constitutes a promising diagnostic, as well as prognostic tool. OncomiRs are miRNAs that promote tumorigenesis, thus inhibiting them by administering antagomiRs is a promising treatment option. Moreover, replacement of the depleted miRNAs is another potential therapeutic approach for HCC. Modification of miRNA levels may also regulate sensitivity to chemotherapeutic agents. Conclusion: miRNA play a pivotal role in HCC pathogenesis and once the underlying mechanisms are elucidated, they will become part of everyday clinical practice against HCC.
Keywords: treatment